Supplying of Products (Herbs) on the EU Market, Imereti Agrozone, Export Opportunities - Lominashvili, Shota; Virsaladze, Naira; Tchanturidze, Irine (European Journal of Sustainable Development, 2019)
Imereti is located in the historical Colchis valley. With its teritory and potential of resourses it is one of the biggest regions in Georgia. The population of the nearby villages of the Rioni River in Imereti region have been following the cultivation of different crops. In the recent past, the greenhouse herbs production is remarkable. The products are distinguished by ecological cleanness and high quality. Within the DCFTA (Deep and Comprehensive Free Trade Area) and SME (Small and medium-sized enterprises ) projects it is important to ensure opportunity of certain products constant delivery to european countries. We have investigated this issue for this purpose. An anonimous research of ordinary people and detailed survey of entrepreneurs involved in exports, about land and other resources, financial issues and rediness of sociaty to start business,was carried out to reveal various problems in this field. Interesting results were received after making statistical analysis and relevant conclusions were made. Specifically, research finds that there are material and labor resources and sustainable climatic conditions for the continuous supply of herbs on the EU market in the Imereti Agrozone. In addition, the creation of green and greenhouse industries requires interested population to provide targeted state support for credit availability, quality seed materials and pest control and irrigation infrastructure. The vital direction is to find sustainable export markets and implement projects supporting the creation of agricultural cooperatives. Keywords: European integration, Export, Imereti agrozone, Financial material and labor resources, Continuous delivery, Standing market